119. A Respiratory Syncytial Virus Prefusion F Protein (RSVPreF3) Candidate Vaccine Administered in Older Adults in a Phase I/II Randomized Clinical Trial Is Well Tolerated. (31st December 2020) - Tica, Jelena; Guiñazú, Javier Ruiz; Andrews, Charles P; Davis, Matthew G; Essink, Brandon; Fogarty, Charles; Kerwin, Edward; Leroux-Roels, Isabel; Steenackers, Katie; Vandermeulen, Corinne; David, Marie-Pierre; Dezutter, Nancy; et al.
Abstract: Background: RSV is a common cause of respiratory acute illness in older adults (OA). We evaluated safety and reactogenicity of RSVPreF3 candidate vaccine in young adults (YA) and OA. Methods: In this phase I/II, placebo-controlled, multi-country trial (NCT03814590), YA aged 18–40 years were randomized 1:1:1:1 and received 2 doses of Low-, Medium- or High-dose of RSVPreF3 non-adjuvanted vaccine, or placebo, 2 months apart. Following favorable safety evaluation, a staggered enrolment with 2 steps followed in OA aged 60–80 years, who were randomized 1:1:1:1:1:1:1:1:1:1 to receive 1 of the 9 RSV vaccine formulations containing Low-, Medium- or High-dose of RSVPreF3 non-adjuvanted or adjuvanted with AS01E or AS01B, or placebo (same schedule). Safety/reactogenicity up to 1 month post-dose 1 are reported here. Results: Exposed set was comprised of 48 YA and 1005 OA. Within 7 days post-dose 1, any solicited/unsolicited adverse event (AE) ranged from 58.3% to 83.3% across YA vaccinees (placebo YA: 58.3%) and from 29.9% to 84.2% across OA vaccinees (placebo OA: 33.7%) (Fig 1). Pain was the most common solicited local AE, being reported in ≤ 58.3% of YA (placebo YA: 0.0%) and at higher rates in the adjuvanted groups (≤ 75.7%) vs non-adjuvanted groups of OA (≤ 14.1%) and placebo OA (4.1%) (Fig 2A). Of solicited general AEs, fatigue (YA: ≤ 41.7% in vaccinees vs 50.0% in placebo; OA: ≤ 48.5% in vaccinees vs 16.3% in placebo) and headache (YA: ≤ 33.3% in vaccinees vs 16.7% in placebo; OA: ≤ 27.7% in vaccinees vs 8.2% in placebo) were most commonly reported (Fig 2B), while fever ≥ 38.0 °C was observed in ≤ 3.0% of OA vaccinees (placebo OA: 0.0%). Grade 3 solicited local and general AEs were observed in OA only, with erythema (≤ 4.9% in vaccinees vs 0.0% in placebo) and fatigue (≤ 2.0% in vaccinees vs 1.0% in placebo) being most common (Fig 2). No serious AEs (SAEs) were reported in YA. A number of 11 OA reported a SAE within 1 month post-dose 1, but none was fatal or assessed as vaccine-related. No clinically significant abnormalities occurred in hematological/biochemical parameters in any group. Figure 1. Percentage of participants presenting at least one type of solicited/unsolicited adverse event (AE) within 7 days post-dose 1 Figure 2. Percentage of participants with at least one type of solicited adverse event (AE) within 7 days post-dose 1 Conclusion: First dose of RSVPreF3 candidate vaccine is well tolerated. AE rates tended to be higher after AS01B -adjuvanted formulations compared to other vaccine formulations. No safety concerns were raised. Funding: GlaxoSmithKline Biologicals SA Disclosures: Jelena Tica, PhD, GSK group of companies (Employee, Shareholder) Javier Ruiz Guiñazú, MD MSc, GSK group of companies (Employee, Shareholder) Charles P. Andrews, MD, GSK group of companies (Scientific Research Study Investigator) Charles Fogarty, MD, GSK group of companies (Grant/Research Support) Edward Kerwin, MD, Amphastar (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)AstraZeneca (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Boehringer Ingelheim (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Chiesi (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Cipla (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)GSK group of companies (Employee, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Mylan (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Novartis (Employee, Advisor or Review Panel member, Research Grant or Support, Speaker's Bureau)other around 40 pharmaceutical companies (Other Financial or Material Support, conducted multicenter clinical research trials)Pearl (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Sunovion (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau)Theravance (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member, Speaker's Bureau) Isabel Leroux-Roels, MD PhD, GSK group of companies (Scientific Research Study Investigator) Corinne Vandermeulen, MD PhD, GSK group of companies (Other Financial or Material Support, My university only received Grant/Research Support) Marie-Pierre David, MSc, GSK group of companies (Employee, Shareholder) Nancy Dezutter, PhD, PharmD, RPh, GSK group of companies (Employee, Shareholder) Laurence Fissette, MSc, GSK group of companies (Employee) Juliane Koch, MD, GSK group of companies (Employee, Shareholder) Narcisa Mesaros, MD, MSc, GSK group of companies (Employee)